Rabbinic study circles : aspects of Jewish learning in its Late Antique context - Hirshman, Marc G.; Satran, David; Reisler, Anita, 1987- (Tübingen, Germany : Mohr Siebeck, 2020)
"Tracing the development of rabbinic education from the first centuries of the Common Era in Palestine through the flowering of centers of learning centuries later in Babylonia, the contributors to this volume examine varied aspects of the educational ethos, the tension between oral tradition and literary practice, and the role of the rabbinic sage as pedagogical innovator and model"--P
A resurgent religion : Midrashic teaching in the first centuries / Marc Hirsham -- Was there really 'an arrogance of wealth'? : re-evaluating a scholarly description of second-century Rabbis / Yael Wilfand -- Sitting or standing? : teaching postures in early Rabbinic literature / Shimon Fogel -- Elijah as Torah teacher : where should one pray? / Adiel Kadari -- The art of forgetting in Rabbinic narrative / Reuven Kiperwasser -- Pirqa tales in the Babylonian Talmud : reality and literature / Eliashiv Fraenkel -- A Rabbinic Irigaray vs. a Christian Wittig? : Boyarin's Parting of the (gender) ways reconsidered / Jonathan Cahana-Blum -- The myth of the Torah / Richie (Shmuel) Lewis.
Includes bibliographical references and indexes.
eBooks on EBSCOhost
Keywords: Jewish learning and scholarship -- History -- To 1500.; Jewish religious education -- History -- To 1500.; Education, Ancient; Éducation antique; Education, Ancient; Jewish learning and scholarship; Jewish religious education; To 1500; History